Prevalence of dental caries and periodontal status among Down's syndrome population in Riyadh City - Khalid Gufran; Omar Saud Alqutaym; Abdul Aziz Maree Alqahtani; Ahmed Mohammed Alqarni; Essa Ali Essa Hattan; Refdan Obeid Alqahtani (Wolters Kluwer Medknow Publications, 2019)
Aim: Aim of the present study was to evaluate the prevalence of dental caries and periodontal status among Down's syndrome population in Riyadh City. Materials and Methods: A total of 81 male Down's syndrome subjects were examined in this study. All subjects were recruited from the Saudi Center for Down Syndrome, Riyadh. Clinical examination was carried out by a single precalibrated examiner. Dental caries experience was counted according to the DMFT (decayed, missing, and filled teeth) indexes. Periodontal status was evaluated by using plaque and gingival indexes. Statistical analysis was performed using SPSS 19 version. Consequently, Pearson chi-square test and Fisher exact test was used to calculate p-value for parametric variables. Results: In this study 11.1% of the subjects were not having any decayed teeth, 39.5% were not having any missing teeth, and 55.6% were not having any filled teeth. In plaque index, maximum number of subjects in all the age group were in the fair group, and there was a highly significant (P value <0.001) association between the age group and the plaque index groups. In gingival index, maximum number of subjects in all the age group was in the poor group. No significant (P value = 0.697) association between the age group and the gingival index groups was found. Conclusion: The present study concluded that the prevalence of dental caries was high and periodontal status of Down's syndrome subjects was poor.